2013
DOI: 10.1108/er-03-2012-0021
|View full text |Cite
|
Sign up to set email alerts
|

Collective employee representation in German companies

Abstract: Purpose -The purpose of this paper is to analyse the distribution and the contextual conditions of statutory and non-statutory forms of employee representation in Germany (works councils and nonstatutory employee representation (NSRs) respectively). It aims to contribute to the debate by proposing a theoretical model which improves our understanding of why works councils and NSRs exist in companies and by presenting an empirical analysis of the explanatory factors based on representative data. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…The Polish study also showed a strong positive relationship between trade union density and the presence of works councils in companies. A similar pattern was also detected in the latest study conducted by Hauser-Ditz et al (2013) in German companies, but the German study used a dummy variable for trade union density (1 if it was higher than 50 percent), in contrast to the continuous measure used in the present paper. The Polish results confirm the persistent influence of trade unions on works councils, although the former no longer hold a monopoly on electing the latter in unionized companies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The Polish study also showed a strong positive relationship between trade union density and the presence of works councils in companies. A similar pattern was also detected in the latest study conducted by Hauser-Ditz et al (2013) in German companies, but the German study used a dummy variable for trade union density (1 if it was higher than 50 percent), in contrast to the continuous measure used in the present paper. The Polish results confirm the persistent influence of trade unions on works councils, although the former no longer hold a monopoly on electing the latter in unionized companies.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, it turned out that firm size and its square are jointly significant. The number of statistically significant variables is relatively small compared to German studies (see: Addison et al, 1997;Addison et al, 2003;Mohrenweiser et al, 2011;Hauser-Ditz et al, 2013). Such results may be due to the fact that works councils have been operating in Poland for only a decade, and their presence in companies has not yet become dependent on a specific pattern of determinants.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…With relatively few pages discussing legal and political regulation or unions and employer organizations as compared to a book on just one of those aspects, Silvia lacks the space to immerse readers in contradictory developments within those parts as well as to systematically address the relations between them. Thus, he only mentions what current empirical research indicates, namely, that “stability” and “erosion” may go hand in hand within industries and even within companies, leading to a pluralization and dualization of industrial relations in Germany (Artus, 2013; Doellgast & Greer, 2007; Hauser-Dietz, Hertwig, & Pries, 2013; Palier & Thelen, 2010).…”
Section: Reviewed By: Jessica Pflueger Institute Of Sociology Friedrich-alexander-universität Erlangen-nürnberg Erlangen Germany Doi: 101mentioning
confidence: 99%